ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU PAKAN SAPI CV SATRIYA FEED LAMPUNG DI KECAMATAN TERBANGGI BESAR KABUPATEN LAMPUNG TENGAH - Dina Wulandari; Sudarma Widjaya; Ani Suryani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
The aims of this research were to analyze a comparison quantity supplies in companies and by calculation EOQ and costs supplies, calculate the supplies safety and calculate the reservations return (reorder point) in cattle feed agroindustry. This research used a case study method in purposively chosen CV Satriya Feeds Lampung. Respondents in this research was the owner of agroindustry. The method of analysis used in this research is quantitative analysis. The results shows that the number of supplies feed cattle raw materials was efficient, but cost supply applied by CV Satriya Feeds Lampung was not efficient, the supplies safety or safety stock according to EOQ analysis, the largest quantity of safety supplies was palm “bungkil” of 27,799.611 kg and the lowest quantity was premix of 809.84 kg. The largest reservation  point was bungkil palm of 33,536.81 kg and the lowestwas premix of 1,102.37 kg. Key words: agroindustry, EOQ, cattle feed, raw materials